The Synonymous Conjugate Personal Names by Profession: Formation, Semantics, Stylistics and Usage - Gaudinskaitė, Danguolė (Acta humanitarica academiae Saulensis, 2021)
The nominal names of persons belong to different categories of formation (for example, the names of persons possessing nominal features, the names of persons by profession, etc.). A total of 1,266 conjugate synonymous nominal derivatives (or possessing one of the components of nominal words) naming the persons by profession were collected from the Dictionary of Lithuanian Language and its electronic version, out of them 386 rows of derivative synonyms (derivative variants) were formed. The derivatives were analysed in terms of formation, semantics, stylistics and usage. To achieve the aim, the methods of derivation, semantic analysis, calculation, descriptive-analytical, substitution were employed. The analysis of the material shows that the rows of derivative synonyms (derivative variants) formed from the names of the persons by profession and close to them derivatives can be divided into semantic groups: denoting an object required for business and work or craft (53,37 per cent of all derivatives); the person’s own business and work or craft, a person who makes a product (36,79 per cent of all derivatives); a place specific to the work (9,84 per cent of all derivatives). The analysis of the empirical material revealed that realia specific to ethnicity can be found in all semantic groups. Names of persons by profession can be associated with forest, plants, agriculture, animals, crafts, etc. The small number of usage of names of persons by profession suggests that they become uncharacteristic of the current language, either because the phenomenon itself no longer exists (then the names of persons also disappear) or because the phenomenon exists, but persons can be named differently (other formations are used).